PENDAMPINGAN MASYARAKAT DESA BARU SUNGAI BETUNG MUDIK KABUPATEN KERINCI DALAM MEREDUKSI KECANDUAN GAWAI PADA ANAK - Harmalis Harmalis; Farid Imam Kholidin; Hengki Yandri; Dosi Juliawati (Universitas Sanata Dharma, 2022)
Gadget addiction in children in the current age of information technology is a global problem experienced almost all over the world, so it is necessary to prevent, reduce and cure solutions for children who are already addicted to gadgets. So the Community Service activities in Desa Baru Sungai Betung Mudik, Kerinci Regency, were carried out assistance to parents in reducing the tendency of gadgets to children. The activity method is carried out in talk shows and psychological consultations for people who need psychological handlers, especially the problem of gadget addiction. This PkM activity was carried out on Friday, February 4, 2022, with activity partners, namely the village community of 30 people. The results of PkM activities show an increase in public understanding and insight into the dangers of gadgets for children if not given wisely, including for the family itself. Then the results of psychological consultations showed that there are parents who complain about their children who are difficult to escape from the device, so it is necessary to do a special follow-up. It is recommended to parents to make a schedule for children to play with gadgets and interact with children, so on for the village government to provide sports facilities for adolescents so that adolescent energy can be channelled positively.